2007
DOI: 10.1002/app.25316
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear properties of NBR/PVC composites

Abstract: Acrylonitrial butadiene rubber (NBR)/Polyvinyl chloride (PVC) composites with different PVC content were prepared. The effect of PVC content on the mechanical strength and tribological properties of the NBR/ PVC composites was investigated. The morphologies of the worn traces and debris of NBR/PVC composites and worn traces of mating ball were observed using a scanning electron microscope (SEM). It was found that the friction and wear of NBR/PVC was lower than that of NBR without PVC. The NBR/PVC composite wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 12 publications
0
21
0
Order By: Relevance
“…It has been widely accepted that the distribution of nano‐CaCO 3 is one of the most important factors in determining the foamability of PP,6 especially for the use of nano‐CaCO 3 because of its large specific surface area and high surface energy 21. The more homogeneous the distribution of nano‐CaCO 3 is, the better the foamability of the nanocomposites will be.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…It has been widely accepted that the distribution of nano‐CaCO 3 is one of the most important factors in determining the foamability of PP,6 especially for the use of nano‐CaCO 3 because of its large specific surface area and high surface energy 21. The more homogeneous the distribution of nano‐CaCO 3 is, the better the foamability of the nanocomposites will be.…”
Section: Resultsmentioning
confidence: 99%
“…They had an average cell diameter in the range of 6.2–12.1 μm, which was smaller than that observed for the PP foam. Many other researchers have reported that blending nanoparticles into PP can improve the foamability 6,17,27…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Among the different types of polymer blends, rubber and plastic blend has been an important one. Huang et al [1] reported that nitrile butadiene rubber (NBR)/polyvinyl chloride (PVC) composite with 30 wt.% PVC showed the best synthetic mechanical and tribological properties, and the lubricating effect of PVC played a role in decreasing the friction coefficient. Ismail et al [2] observed that the vulcanized PP/NBR blend had perfect tensile properties and oil resistance, and it was able to withstand serious natural weathering conditions.…”
Section: Introductionmentioning
confidence: 99%